Robotic Versus Laparoscopic Radical Hysterectomy in Cervical Cancer Patients: A Matched-Case Comparative Study. Issue 8 (1st October 2014) - Kim, Tae-Hyun; Choi, Chel Hun; Choi, June-Kuk; Yoon, Aera; Lee, Yoo-Young; Kim, Tae-Joong; Lee, Jeong-Won; Bae, Duk-Soo; Kim, Byoung-Gie
Abstract : Objective: This study aimed to compare initial surgical outcomes and complication rates of patients with early-stage cervical cancer who underwent robotic radical hysterectomy (RRH) and conventional laparoscopic radical hysterectomy (LRH). Methods: Patients diagnosed with invasive cervical cancer (International Federation of Gynecology and Obstetrics stage I-IIA) who underwent RRH (n = 23) at Samsung Medical Center from January 2008 to May 2013 were compared with matched patients who underwent LRH (n = 69) during the same period. The 2 surgical groups were matched 3:1 for variables of age, body mass index, International Federation of Gynecology and Obstetrics stage, histological subtype, tumor size, and node positivity. All patient information and surgical and postoperative follow-up data were retrospectively collected. Results: Operating time was significantly longer (317 vs 236 minutes; P < 0.001) in the RRH group compared with the LRH group but mean estimated blood loss was significantly reduced in the RRH group (200 vs 350 mL; P = 0.036). Intraoperative and postoperative complications were not significantly different between the 2 groups (4.3% for RRH vs 1.45% for LRH; P = 0.439). Recurrences were 2 (8.7%) in the RRH and 7 (10.1%) in the LRH group. The overall 3-year recurrence-free survival was 91.3% in RRH group and 89.9% in the LRH group ( P = 0.778). Conclusions: Although operating time was longer in the RRH cases because of lesser experience on robotic platform, we showed that surgical outcomes and complication rate of RRH were comparable to those of LRH. In addition, surgical skills for LRH easily and safely translated to RRH in case of experienced laparoscopic surgeon.